TRIBAL COMMUNITY AND DISASTER RESILIENCE: BAJO COMMUNITY AND THEIR COPING STRATEGY TO CYCLONE IN MUNA BARAT DISTRICT - Dina Ruslanjari; Titis Puspita Dewi; Anisa Eka Puspitasari (Universitas Gadjah Mada, 2019)
Muna Barat District is a prone area to natural disasters, such as earthquakes and tidal waves. The cyclone and tidal waves often occur and those two phenomena occur during the transition season (from the dry to the rainy season). This research aims to analyse the vulnerability and capacity related to the readiness of the community of Bajo Tribe to face the cyclone . The method being applied in this research is quantitative descriptive. Furthermore, the village that are selected purposively are those where located on the sea and hit by the cyclone. The sample chosen is the head of family of Bajo Tribe. Vulnerability and capacity are counted with Analytical Hierarchy Process (AHP) weighting in determining the priority scale or the most preferred alternative choice. The result of this research is Tiga, Bero, Tasipi, and Katela Village are categorized as medium vulnerability and Mandike Village has low vulnerability. Tiga, Bero, Tasipi, Mandike, and Katela Village are classified as medium capacity.